Effects of membrane lipid composition on Mycobacterium tuberculosis EsxA membrane insertion: A dual play of fluidity and charge. (September 2019) - Ray, Supriyo; Vazquez Reyes, Salvador; Xiao, Chuan; Sun, Jianjun
Abstract: As a key virulence factor of Mycobacterium tuberculosis, EsxA or 6-kDa early secreted antigenic target (ESAT-6) has been implicated in phagosome rupture and mycobacterial translocation from the phagosome to the cytosol within macrophages. Our previous studies have shown that EsxA permeabilizes liposomal membrane at acidic pH and a membrane-permeabilization defective mutant Q5K attenuates mycobacterial cytosolic translocation and virulence in macrophages. To further probe the mechanism of EsxA membrane permeabilization, here we characterized the effects of various lipid compositions, including biologically relevant phagosome-mimicking lipids and lipid rafts, on the structural stability and membrane insertion of EsxA WT and Q5K. We have found a complex dual play of membrane fluidity and charge in regulating EsxA membrane insertion. Moreover, Q5K affects the membrane insertion through a structure- and lipid composition-independent mechanism. The results of this study provide a novel insights into the mechanism of EsxA membrane interaction.